A Biofilm Matrix-Associated Protease Inhibitor Protects Pseudomonas aeruginosa from Proteolytic Attack - Boo Shan Tseng (American Society for Microbiology, 2018)
ABSTRACT Pseudomonas aeruginosa produces an extracellular biofilm matrix that consists of nucleic acids, exopolysaccharides, lipid vesicles, and proteins. In general, the protein component of the biofilm matrix is poorly defined and understudied relative to the other major matrix constituents. While matrix proteins have been suggested to provide many functions to the biofilm, only proteins that play a structural role have been characterized thus far. Here we identify proteins enriched in the matrix of P. aeruginosa biofilms. We then focused on a candidate matrix protein, the serine protease inhibitor ecotin (PA2755). This protein is able to inhibit neutrophil elastase, a bactericidal enzyme produced by the host immune system during P. aeruginosa biofilm infections. We show that ecotin binds to the key biofilm matrix exopolysaccharide Psl and that it can inhibit neutrophil elastase when associated with Psl. Finally, we show that ecotin protects both planktonic and biofilm P. aeruginosa cells from neutrophil elastase-mediated killing. This may represent a novel mechanism of protection for biofilms to increase their tolerance against the innate immune response. IMPORTANCE Proteins associated with the extracellular matrix of bacterial aggregates called biofilms have long been suggested to provide many important functions to the community. To date, however, only proteins that provide structural roles have been described, and few matrix-associated proteins have been identified. We developed a method to identify matrix proteins and characterized one. We show that this protein, when associated with the biofilm matrix, can inhibit a bactericidal enzyme produced by the immune system during infection and protect biofilm cells from death induced by the enzyme. This may represent a novel mechanism of protection for biofilms, further increasing their tolerance against the immune response. Together, our results are the first to show a nonstructural function for a confirmed matrix-interacting protein.